A Case Report of Acute Hemolysis after Endovascular Abdominal Aneurysm Repair with Onyx Embolization of Endoleak: A Clinical Conundrum - Choudhury, Apratim Roy; Valakkada, Jineesh; Ayappan, Anoop; Alex, Ajay (Journal of Clinical Interventional Radiology ISVIR, 2025)
A 75-year-old gentleman with a large degenerative abdominal aortic aneurysm of diameter 7.5 cm underwent standard endovascular aneurysm repair with Endurant (Medtronic) stent graft. He underwent coil embolization of a small penetrating ulcer in the neck of the aneurysm, followed by liquid embolic agent (Onyx 18) injection in the aneurysm sac in view of endoleak. The procedure was uneventful with <100 mL blood loss. However, in the postoperative period, the patient developed a drop in hemoglobin levels with a rising trend of indirect bilirubin and reticulocyte count—suggestive of acute hemolysis. He was managed conservatively with blood transfusion and recovered well. In this case, the one cause of hemolysis could be mechanical damage to the red blood cells by the bare metal part of the stent and the tortuosity of the iliac vessels. No such previous report of acute hemolysis after aortic stent graft deployment has been previously reported.
Keywords: EVAR; abdominal aortic aneurysms; stent graft; hemolysis